Biliary Strictures Are Associated With Both Early and Late Hepatic Artery Stenosis. Issue 1 (January 2021) - Hann, Angus; Seth, Rashmi; Mergental, Hynek; Hartog, Hermien; Alzoubi, Mohammad; Stangou, Arie; El-Sherif, Omar; Ferguson, James; Roberts, Keith; Muiesan, Paolo; Oo, Ye; Issac, John R.; et al.
Abstract : Background: Hepatic artery stenosis (HAS) following liver transplantation results in hypoperfusion and ischemic damage to the biliary tree. This study aimed to investigate how vascular intervention, liver function test derangement, and time point of HAS onset influence biliary complications. Methods: A single-center retrospective study of adult patients that underwent primary liver transplantation. Patients were grouped according to the presence or absence of HAS and then into early (⩽90 d) or late (>90 d) subgroups. Biliary complications comprised anastomotic (AS) or non ASs (NASs). Results: Computed tomography angiography confirmed HAS was present in 39 of 1232 patients (3.2%). This occurred at ⩽90 and >90 days in 20 (1.6%) and 19 (1.5%), respectively. The incidence of biliary strictures (BSs) in the group with HAS was higher than the group without (13/39; 33% versus 85/1193; 7.1%, P = 0.01). BS occurred in 8/20 (40.0%) and 5/19 (26.3%) of the early and late groups, respectively. The need for biliary intervention increased if any liver function test result was ≥3× upper limit of normal ( P = 0.019). Conclusions: BS occurs at a significantly higher rate in the presence of HAS. Onset of HAS at ⩽90 or ≥90 days can both be associated with morbidity. Significant liver function test derangement at HAS diagnosis indicates a higher likelihood of biliary intervention for strictures.